Efektivitas Latihan Birth Ball Terhadap Penurunan Nyeri Persalinan Kala I Fase Aktif pada Primigravida - Ade Kurniawati; Djaswadi Dasuki; Farida Kartini (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
Some problems may appear due to childbirth, such as discomfort, fear and pain. Particularly for pain in the first stage of labor, it can be severe and takes place a longer time, thus, pain management is necessary. Birth ball exercise is one of nonpharmacological methods to reduce labor pain.This was a quasi-experimental study to determine the effectiveness of birth ball exercise isone of nonpharmacological methodstowards the reduction of labor pain in the active phase of the first stage of labor in primigravida. Thirty eight women were recruited with consecutive sampling technique, divided into 2 groups, the treatment group given ball birth exercise in active phase of the first stage for 30 minutes for two times and the control group not given the exercise. The bivariable analysis was conducted with correlation and t-test, while the multivariable analysis used linear regression. The results showed that the mean labor pain in the group given birth ball exercise was lower 4.5 than that in the control group at 5.4 with a p-value of 0.01. The extraneous variables that influenced labor pain were anxiety, husband and family support with a p-value of <0.05. The multivariate analysis using Model 4 obtained an R² value of 0.49, which means that the birth ball exercise and husband and family support contributed to labor pain equal to 49%.There were significant differences in pain intensity in active phase of the first stage of labor between primigravida who practiced birth ball exercise and those who did not. The pain intensity was lower in women practicing birth ball exercise than that in those who did not.